Influence of Body Image in Women Undergoing Treatment for Breast Cancer - Ana Carolina Lagos Prates; Ruffo Freitas-Junior; Mariana Ferreira Oliveira Prates; Márcia de Faria Veloso; Norami de Moura Barros (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2017)
Abstract Objective The objective of this study was to investigate the self-esteem of women with and without breast cancer regarding their body image. Methods A quantitative, case-control study in which 90 women with breast cancer were evaluated in the case group, and 77 women without breast cancer in the control group. For data collection, the body satisfaction scale (BSS), a scale adapted and validated in Brazil, and the Rosenberg self-esteem questionnaire were used. For the statistical analysis of the data, the Statistical Package for the Social Sciences software (IBM-SPSS, Chicago, Il, US), version 16.0 was used. Results Compared with the women without breast cancer, those with breast cancer were more dissatisfied with body image related to appearance. Women undergoing neoadjuvant chemotherapy were more dissatisfied with their appearance compared with those with cancer who were not undergoing this treatment. Mastectomy also accounted for more dissatisfaction concerning appearance among women who underwent the procedure compared with the women who were submitted to breast-conserving therapy. Conclusion Women with breast cancer were more dissatisfied with their body image compared with those without breast cancer, particularly following mastectomy or during chemotherapy. The self-esteem was found to be negatively affected in patients who were dissatisfied with their body image.